The Effect of Teaching Vocabulary Using Picture on the Second Grade Students’ Vocabulary Mastery - Zulkifli Zulkifli (Language-Edu, 2019)
ABSTRACTZulkifli.2019, The Effect of Teaching Vocabulary Using Picture on The Second Grade Students’ Vocabulary Mastery Thesis. English Department, Graduate Program.University of Islam Malang.Advisor Dr. H. Nur Salam, M.Pd.,                                      The objectives of this research are to know the significant at students ‘on teaching Vocabulary using traditional way and using picture way in mastery vocabulary.The research employed experimental and control group, which consisted of 48 students MTS. The students were put into two groups; twenty four students were put into the experimental groups and another twenty four students were put into control groups. The instrument was test items, administered to the both groups. The data was analyzed with mean score and t-test formula. The result of this research showed that the significant of the students taught of vocabulary by using picture (experimental groups) was better in the post –test showed that out of 24 students and the achievement of the students of control group was at fair standard 24 students classified. This revealed that there was a significant of the experimental group and control group. In the table of significance, it can be seen that on the df = 46 students and the degree of significance 5% the value of degree of significance is 337.31 by comparing the value tois bigger thantt. The result of t-test (to) shows that t-test (t0) > t-table (tt) (337, 31> 2.021). It means that the students who taught by media on students’ vocabulary in experimental group is better that students taught without using media.  Key Words:  Teaching Vocabulary using picture vocabulary mastery